2022
DOI: 10.1002/vetr.1632
|View full text |Cite
|
Sign up to set email alerts
|

Association between a genetic index for lameness resistance and the incidence of claw horn lesions in Holstein cows

Abstract: Background This study aimed to determine the association between the lameness advantage genetic index and four outcomes: sole haemorrhage (SH), sole ulcers (SU), white line lesions (WL), and lameness during mobility scoring. Methods We enrolled 2352 Holstein cows from four predominantly housed dairy herds in the UK. Cows were mobility scored and foot lesions recorded at four time points from before calving to late lactation. Cows were genotyped and genetic indexes were assigned to each cow following national g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…An increased foot angle at T2-calving was not significantly associated with either sole lesion or white line lesion development in the multivariable analysis. Foot angle is included in the lameness advantage index, which is associated with the incidence of sole hemorrhage, sole ulcers, and lameness ( Barden et al, 2022 ). van Dorp et al (2004) highlighted that cows with a steeper foot angle trait had genetically significantly better locomotion, while Kougioumtzis et al (2014) found that an intermediate foot angle breeding trait was related to reduced lameness, with a steeper angle preferable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased foot angle at T2-calving was not significantly associated with either sole lesion or white line lesion development in the multivariable analysis. Foot angle is included in the lameness advantage index, which is associated with the incidence of sole hemorrhage, sole ulcers, and lameness ( Barden et al, 2022 ). van Dorp et al (2004) highlighted that cows with a steeper foot angle trait had genetically significantly better locomotion, while Kougioumtzis et al (2014) found that an intermediate foot angle breeding trait was related to reduced lameness, with a steeper angle preferable.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the development of CHDL is multifactorial, representing the interrelationship of genetic ( Barden et al, 2022 ; Li et al, 2023 ), anatomic, management ( Griffiths et al, 2018 ), and environmental components ( Barker et al, 2009 ; Rutherford et al, 2009 ; Solano et al, 2015 ). The objective of the present study was to assess claw anatomy and sole temperature and their association with CHDL by examining key measurements during the transition period and the subsequent development of sole and white line lesions during early lactation in a large cohort of well-monitored UK dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…WE wish to follow up on our recent study 1 where we aimed to evaluate the lameness advantage genetic index by quantifying its association with claw horn lesions and lameness in 2352 Holstein cows. A secondary objective was to screen all genetic indexes (other than lameness advantage) for an association with the same outcomes, which showed that both feet and legs and locomotion (assessed in type classification) were associated with lameness, but not with claw horn lesions.…”
mentioning
confidence: 99%
“…As mobility scoring has a limited sensitivity to detect foot lesions, likely due in part to an evolutionary advantage of cattle masking signs of pain, it is important not to exacerbate this problem with genetic selection. Lameness advantage is associated with both sole lesions and lameness, as well as infectious lesions; 2 we believe this is the best option for those aiming to improve foot health through selective breeding.…”
mentioning
confidence: 99%
See 1 more Smart Citation